Con « m » de « mamá » : las militantes comunistas y la Unión de Mujeres Argentinas durante la segunda mitad del siglo XX - Natalia Casola (Amnis)
This article analyzes the characteristics of the policy developed by the Argentine Communist Party towards women from the Second World War until the end of the military dictatorship in 1983. This research has two main objectives. First, to analyze how the overall strategy of the party was translated -- the so-called » democratic revolution » --- at the level of the women's organization by building the Union of Argentine Women (Unión de Mujeres Argentinas, UMA). Secondly, to examine what gender roles the organization reproduced and what militant bias it produced specifically in the context of the 1960s and 1970s, years of strong political radicalization in Argentine left-wing.